PENGARUH KOMPENSASI, LINGKUNGAN KERJA DAN PELATIHAN TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. AGRI ANDALAS KECAMATAN AIR PERIUKAN KABUPATEN SELUMA - Kusnadi, Ary; Sismanto, Adi (Yayasan Insani Mandiri Santani, 2023)
The population used in this research is all employees who work at PT Angri Andalas, Air Periukan District, Seluma Regency. 150 respondents. The sampling technique used total sampling based on predetermined criteria of 150 respondents. Data collection techniques are observation, documentation and questionnaires. The processed data was analyzed using the SPSS 24 formula. Based on the results of research and analysis of the influence of the Compensation, Work Environment and Training variables on Employee Job Satisfaction. The following conclusions can be drawn: Compensation has a positive effect on Employee Job Satisfaction of employees, this is proven by hypothesis testing with the t-test, obtained tcount > ttable (6,229 > 1,980) The work environment has a positive effect on Employee Job Satisfaction of employees, this is proven by hypothesis testing with the t-test, obtained tcount > ttable (2,240>1,980) Training has a positive effect on Employee Job Satisfaction of employees, this is proven by hypothesis testing with the t-test, obtained tcount > ttable (3,084>1,980) Compensation, Work Environment, and Training (X3) influence employee Job Satisfaction. This can be seen from joint hypothesis testing (Simultaneous) Ftable > Fcount (68,710 > 3,940). This is proven by the correlation analysis R = 0.765 (76.5%) and is almost close to 1. And the coefficient of determination is R2 = 0.585 or around 58.5% while 41.5% is the contribution of other variables not studied. Keyword: Kompensasi, lingkungan dan Kepuasan